FORMULASI TEPUNG JAGUNG (Zea corn L.) TERFERMENTASI DAN TEPUNG TERIGU TERHADAP SIFAT KIMIA, FISIKOKIMIA DAN SENSORI ROTI MANIS [Formulation of Fermented Corn (Zea corn L.) Flour and Wheat Flour on The Chemical, Physicochemical and Sensory Properties of Sweet Bread] - Setyani, Sri; Yuliana, Neti; Maesari, Siti (Jurnal Teknologi & Industri Hasil Pertanian, 2016)
The purpose of this research was to find the best formulation ofÂ  fermented corn flour and wheat flour to produceÂ  chemically, physicochemically and organoleptically acceptable sweet breads.Â  The formulationÂ  consisted of 6 levels ratio of 100% corn tempe flour and wheat flour: L1 (0%: 100%); L2 (5%: 95%); L3 (10%: 90%); L4 (15%: 85%); L5 (20%: 80%); and L6 (25%: 75%) w/w with 4 replications. The experiment was Â Â arranged in a Complete Randomized Block Design (CRBD).Â  Data were analysed using analysis of variance, further were tested by using Honestly Significant Difference (HSD) test in 5% level of significance. Â Â The results showed that the addition of fermented corm increased sweet breadâs levels of ash, fat, flavor and aroma values.Â  While the moisture and protein contents, doughâs volume, color, texture as well as overall acceptance values decreased.Â  The best formula was obtainedÂ  from Â L2 (5% fermented corn : 95% wheat flour) whith the characteristics of Â 24.41% Â muoisture, 1,55% ash, 10.66% fat, 17.397% protein contents, and 65.5% Â development of dough volume. The sweet breads Â score of texture was Â 3.09 (soft), taste and aroma score was 3.02 (rather typical corn), color score was 2.05 (yellowish brown), and the overall acceptance Â score was Â 3.43 (like).Keywords :Â Â  fermented corn,Â  flour, sweet bread, wheat